Improving the cuttings transport performance of water-based mud through the use of polypropylene beads - Onuoha, M.D.U.; Ismail, I.; Piroozian, A.; Mamat, N.S.; Ismail, A.S. (Universiti Kebangsaan Malaysia, 2015)
This research work presents the experimental results of the effect of polypropylene beads’ concentrations in water-based mud on wellbore cleaning. A comparative study of cuttings transport performance (CTP) of water-based mud and water-based mud with polypropylene beads were carried out at different hole angles of 0°, 30°, 60°. 75° and 90° in a 13 ft (3.96 m) acrylic concentric annulus flow test section, having a 2 in (50.8 mm) casing ID and a fixed 0.79 in (20 mm) inner pipe OD. A total of 100 runs had been accomplished using fine sands (from Tanjung Balau, Johor Bahru, Malaysia), of size ranging from 5/127 - 6/127" (1.0 – 1.2 mm) and density 2.4 g/cc (2400 kg/m3), with the mud density and viscosity maintained at 9 ppg (1078 kg/m3) and 5 cp (0.005 Pa.s), respectively, in a flow velocity of 2.1 ft/s (0.64 m/s). Polypropylene beads used in this study have the following properties: 290 kg/cm2 of tensile strength at yield, 0.86 g/cc (860 kg/m3) density, 4 mm (20/127") size, 82 R scale Rockwell hardness, 13,500 kg/cm2 flexural modulus, 85°C heat deflection temperature at 4.6 kg/cm2, 4 g/10 min melt flow rate at 230°C and spherical in shape. The experimental findings showed that commingling the basic mud with polypropylene beads has successfully introduced a buoyant force which was found to have improved the cuttings transport performance by more than 10% when weight concentration of the polypropylene beads was increased to 1.5% as compared with the performance obtained from the basic water-based mud. The improvement of cuttings transport performance was found to be more significant in a vertical hole.